Economic viability of peanut production on leased land in the Jaboticabal region of São Paulo state, Brazil - David Ferreira Lopes Santos; Bruna Luísa da Silva; Juliana Borba de Moraes Farinelli; Kandy Horita; Camila Aparecida Fonseca Souza; Stela Basso Montoro (Agro@mbiente On-line, 2019)
Peanut cultivation has been used as a rotation crop in sugarcane renewal areas in São Paulo, state, Brazil. This practice guarantees agronomic and economic benefits to the region in a way complementary to the sugarcane crop. Small- and medium-sized rural producers have specialized in the cultivation of peanuts in the of renewal sugarcane areas, with production mainly occurring via a lease contract system. Thus, the objective of this study is to analyze the economic viability of commercial and productive operations associated with the peanut cultivation in leased areas. From a delimitated production profile modal, it was possible to analyze economic viability by triangulating secondary and primary information for peanut cultivation in Jaboticabal, the city of greatest production of this oil-giving seed in Brazil. Using Net Present Value, Internal Rate of Return, Return on Investment and Point of Equilibrium techniques, it was possible to show that the peanut crop is operationally feasible. However, financial and economic viability only occurred when leases cost equal or less than 50 sacks per hectare and when the producer was able to work with an area equal to or greater than 91 hectares (the break-even point). These results bring new economic information, supplementing that already in literature and provides data necessary for the rural producer to plan of production and size of investment.